Immunohistochemical Detection of BRAFV600E in Cutaneous Melanocytic Neoplasms in a Cohort of Egyptian Population - M. Yakout, Nada; M Abdallah, Dina; A Abdelmonsif, Doaa; Mahmoud Kholosy, Hassan; Elsakka, Omayma (Asian Pacific Journal of Cancer Care, 2022)
Objective: Melanocytic neoplasia shows different pathways that have been implicated in tumorigenesis. One of the key genes involved in the BRAFV600E gene, can be detected through DNA-based or protein-based tests including immunohistochemistry (IHC). To check its reproducibility, this study was conducted to evaluate BRAFV600E IHC by different observers in a range of melanocytic neoplasms. Methods: The present study was performed to evaluate immunohistochemical staining (IHC) using the RM-08 to detect BRAF V600E in 50 formalin-fixed paraffin-embedded (FFPE) blocks of different melanocytic neoplasms after bleaching using Tris-HCL buffer. IHC was considered positive when more than 90% of tumour cells showed cytoplasmic staining. IHC assessment by a team of two pathologists and a third pathologist to check the interobserver variability. IHC scores were compared among nevi and melanoma. Results: IHC evaluation revealed good agreement by different observers (ĸ-coefficient=0.691, p=0.00). BRAFV600E showed a statistically significant difference between nevi and melanoma. Conclusions: These findings suggest that BRAFV600E IHC assessment shows good reproducibility among pathologists, however, more strict criteria should be adopted in interpretation, especially in bleached samples.